2015
DOI: 10.2337/db15-0441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Weight Loss and Regain With Lifestyle Intervention: Analyses From the Diabetes Prevention Program and the Look AHEAD Randomized Controlled Trials

Abstract: Clinically relevant weight loss is achievable through lifestyle modification, but unintentional weight regain is common. We investigated whether recently discovered genetic variants affect weight loss and/or weight regain during behavioral intervention. Participants at high-risk of type 2 diabetes (Diabetes Prevention Program [DPP]; N = 917/907 intervention/comparison) or with type 2 diabetes (Look AHEAD [Action for Health in Diabetes]; N = 2,014/1,892 intervention/comparison) were from two parallel arm (lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 32 publications
3
58
0
Order By: Relevance
“…Nevertheless, there is some evidence that "healthy" diets modify the impact of individual BMI-associated variants in observational studies (30) and clinical trials (31). Interactions have been reported between BMI-associated genetic risk scores and diverse exposures including sugarsweetened beverages (32), fried foods (33), and television viewing (34), though replication data are sparse.…”
Section: Genetics and Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is some evidence that "healthy" diets modify the impact of individual BMI-associated variants in observational studies (30) and clinical trials (31). Interactions have been reported between BMI-associated genetic risk scores and diverse exposures including sugarsweetened beverages (32), fried foods (33), and television viewing (34), though replication data are sparse.…”
Section: Genetics and Dietmentioning
confidence: 99%
“…However, such studies are challenging to perform and interpret (41) and need further replication. Despite promising epidemiological data, the largest clinical trial analysis found no evidence that FTO variation influences weight loss after lifestyle intervention (31).…”
Section: Genetics and Energy Expenditurementioning
confidence: 99%
“…Within 1 year, 50% of people who engage in a weight‐loss intervention will experience weight regain (Palascha, van Kleef, & van Trijp, ). Current research indicates weight maintenance and regain are complex, and affected by the interaction of a variety of physiologic, genetic, and psychosocial factors (Brantley et al., ; Palascha et al., ; Papandonatos et al., ; Rogge & Gautam, ). Studies to determine more effective strategies to promote and maintain weight loss are ongoing; emerging results may offer insight.…”
Section: Need For Improved Training Resources and Reimbursementmentioning
confidence: 99%
“…This gene has also been identified as an obesity susceptibility gene due to its relationship with BMI (74,75) . Papandonatos and colleagues showed that the G allele of the MTIF3 rs1885988 was associated with greater weight loss following lifestyle intervention over 4 years of follow-up (76) . In other words, their result implies that G allele of the MTIF3 rs1885988 is related to lower-risk of weight regain.…”
Section: Nutrient Metabolism-related Genes and Their Association Withmentioning
confidence: 99%